FoxO Transcription Factor Regulate Hormone Mediated Signaling on Nymphal Diapause - Zhen-Juan Yin; Xiao-Lin Dong; Kui Kang; Hao Chen; Xiao-Yan Dai; Guang-An Wu; Guang-An Wu; Li Zheng; Yi Yu; Yi-Fan Zhai; Yi-Fan Zhai; Yi-Fan Zhai (Frontiers in Physiology, 2018)
Diapause is a complex physiological adaptation phenotype, and the transcription factor Forkhead-box O (FoxO) is a prime candidate for activating many of its diverse regulatory signaling pathways. Hormone signaling regulates nymphal diapause in Laodelphax striatellus. Here, the function of the FoxO gene isolated from L. striatellus was investigated. After knocking-down LsFoxO in diapausal nymphs using RNA interference, the titers of juvenile hormone III and some cold-tolerance substances decreased significantly, and the duration of the nymphal developmental period was severely shorted to 25.5 days at 20°C under short day-length (10 L:14 D). To determine how LsFoxO affects nymphal diapause, analyses of RNA-sequencing transcriptome data after treatment with LsFoxO–RNA interference was performed. The differentially expressed genes affected carbohydrate, amino acid and fatty acid metabolism, and phosphatidylinositol 3-kinase/protein kinase B signaling pathway. Thus, LsFoxO acts on L. striatellus nymphal diapause and is, therefore, a potential target gene for pest control. This study may lead to new information on the regulation of nymphal diapause in this important pest.